2016
DOI: 10.1007/s11032-016-0497-4
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis for the identification of candidate genes controlling phenolic compound accumulation in broccoli (Brassica oleracea L. var. italica)

Abstract: Quantitative trait loci (QTL) analysis of phenolic compound accumulation was performed in a broccoli mapping population (Brassica oleracea) saturated with single nucleotide polymorphism markers from an Illumina 60K array designed for rapeseed (Brassica napus). In 2 years of analysis in North Carolina and 1 year in Illinois, variation in total phenolic content and antioxidant capacity was associated with 60 QTL. Twenty-three of these loci were identified in at least two analyses (three phenolic/ antioxidant ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…These stable lines will be the foundation for future work in identifying the causative mutation and gene for the white pupae phenotype. As in previous studies which identified candidate genes that govern traits of interest ( Kloosterman et al 2010 ; Ahsan et al 2013 ; Gardner et al 2016 ), whole-genome resequencing and RNA-seq analysis of individuals from this common genetic background segregating for white and wild-type brown pupae will facilitate the characterization of additional candidate genes and mutations involved in the phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…These stable lines will be the foundation for future work in identifying the causative mutation and gene for the white pupae phenotype. As in previous studies which identified candidate genes that govern traits of interest ( Kloosterman et al 2010 ; Ahsan et al 2013 ; Gardner et al 2016 ), whole-genome resequencing and RNA-seq analysis of individuals from this common genetic background segregating for white and wild-type brown pupae will facilitate the characterization of additional candidate genes and mutations involved in the phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Specific QTLs may be identified for desirable microgreens related traits (shelf life and nutrients content: Fe, Zn) in particular crop on the basis of contrasting parents and corresponding data of Genomics. The Quantitative Trait Loci have been identified for phytoactive compounds, iron, zinc and shelf-life related microgreen traits incabbage ( Wu et al, 2008 ), broccoli ( Gardner et al, 2016 ), wheat ( Krishnappa et al, 2022 ), lettuce ( Hayashi et al, 2012 ), melon ( Dai et al, 2022 )and chickpea ( Mahto et al, 2022 ).…”
Section: Strategies To Overcome Limitations Of Microgreen Productionmentioning
confidence: 99%
“…Brassica is a genus with many beneficial characteristics for our health, such as reducing risk for age related chronical illness, degenerative diseases and it reduces risk of several types of cancer. Brassica contain many vitamins which are essential for our health, such as vitamin A, C, E, K and B-6, carotenoids (such as c-and b-carotene and zeaxanthin), anthocyanins, folate, soluble sugars and phenolic compounds which are known to be the major antioxidants of Brassica crops [1].…”
Section: Brassicaceae Familymentioning
confidence: 99%